The association between global and prime diet quality scores and the odds of metabolic-associated fatty liver disease: a case-control study - Zacharakis, Georgios; Alyami, Hanan; Alrasheed, Tariq; Almutairi, Naif S.; Gomaa Shehab, Gaber Mohamed; Elbqry, Mohamed Goda; Ali Alotni, Majid (Frontiers in Nutrition, 2025)
BackgroundMetabolic-associated fatty liver disease (MAFLD) is a leading cause of chronic liver disease worldwide, which is closely linked to poor dietary habits, obesity, and metabolic dysfunction. The Global Diet Quality Score (GDQS) and Prime Diet Quality Score (PDQS) are newly developed tools for assessing diet quality across diverse populations. However, evidence on their relationship with MAFLD remains limited. This study aimed to investigate the association between GDQS and PDQS and the odds of MAFLD using a case–control design.MethodsWe conducted a case–control investigation at Prince Sattam bin Abdulaziz University Hospital, Al-Kharj, Saudi Arabia, with participant enrollment from February 2023 to January 2025. The study cohort consisted of 225 cases and 225 controls. Dietary intake was assessed using a semi-quantitative food frequency questionnaire to calculate GDQS and PDQS. Cases and controls were matched by age (±3 years). An unconditional logistic regression analysis was performed to estimate odds ratios (ORs) and 95% confidence intervals (CIs).ResultsCases had lower GDQS and PDQS compared to controls (p < 0.001), with a higher consumption of refined grains and sugar-sweetened beverages and a lower intake of fruits, vegetables, and legumes. Each 1-SD increase in the GDQS and PDQS was associated with approximately 40% lower odds of MAFLD (OR = 0.61; 95% CI: 0.47, 0.79 and OR = 0.60; 95% CI: 0.46, 0.79, respectively).ConclusionHigher GDQS and PDQS scores are associated with reduced MAFLD risk, suggesting that improving diet quality could be a key strategy for MAFLD prevention in clinical and public health settings.